Расчет суммарных газодинамических характеристик компрессоров по идентифицированной модели с использованием CFD-технологий - Спицын, В. Е.; Шаровский, М. А.; Ивченко, А. В.; Токарева, Е. А.; Шелковский, М. Ю. (Eastern-European Journal of Enterprise Technologies, 2009)
Issues related identification of 1-D gas dynamic characteristics based on stage mapping using CFD technologies are addressed in this paper. Compressor of GT25000 gas turbine engine developed and manufactured at «Zorya»-«Mashproekt» SC GTRPC is taken as a test object. Methods developed and described in this paper enable to obtain full scale total gas dynamic compressor characteristics at low processing time